2007
DOI: 10.1111/j.1467-9507.2007.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Interparental Conflict and Preschoolers’ Peer Relations: The Moderating Roles of Temperament and Gender

Abstract: The relations between destructive interparental conflict (IPC) and three-to six-yearolds' ( N = 62) peer relations were examined as a function of child temperament and gender. Regression analyses indicated that effortful control moderated the relations of IPC with children's amount of peer interaction as well as with their problematic relations with peers. Specifically, high IPC was associated with low amount of interaction and high problematic relations for preschoolers low in effortful control, but it was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 85 publications
5
27
0
4
Order By: Relevance
“…Aggressive/ rejected children were defined as having a difficult temperament, and they developed sociably unsuitable entry strategies into their peer group. Results of a study conducted on 62 children, aged between 3 and 6, to analyse their peer relations in terms of child temperament (David & Murphy, 2007) are similar to results obtained from this study; child temperament has a predictor effect on peer relations of children. Preschool children, who require less effortful control, experience adverse peer relations in comparison to children who require a higher level of effortful control.…”
Section: Discussionsupporting
confidence: 85%
“…Aggressive/ rejected children were defined as having a difficult temperament, and they developed sociably unsuitable entry strategies into their peer group. Results of a study conducted on 62 children, aged between 3 and 6, to analyse their peer relations in terms of child temperament (David & Murphy, 2007) are similar to results obtained from this study; child temperament has a predictor effect on peer relations of children. Preschool children, who require less effortful control, experience adverse peer relations in comparison to children who require a higher level of effortful control.…”
Section: Discussionsupporting
confidence: 85%
“…Other subject-related studies also obtained similar results (Bierman, 2005;David, 2004;Erwin, 1993) in favor of boys. Boys can exhibit stricter, more oppressive, verbal, and physical aggression toward peers in comparison to girls.…”
Section: Gendersupporting
confidence: 81%
“…Studies of elementary students characteristically have shown that boys exhibit less closeness and more conflict in their relationships with teachers (Baker, 2006;Birch & Ladd, 1997Hughes, Cavell, & Willson, 2001;Kesner, 2000;Murray & Murray, 2004), and data available in Baker, Hughes et al, and Murray and Murray have shown these differences to be characterized by small (for closeness) to medium-size (for conflict) effects for boys versus girls in kindergarten through fifth grade. Given the tendency for boys to exhibit differences in both language competence (see Pence & Justice, 2007) and control attributes (see David & Murphy, 2007) relative to girls, this study considered whether gender moderated the relationships between language competence and the teacher-child relationship and between temperamentally based child attributes and the teacher-child relationship. In sum, the questions addressed in this study were threefold: (a) To what extent do preschoolers' language skills, temperamentally based attributes, and gender predict teacher-child relationship quality?…”
Section: Predictors Of Teacher-child Relationship Qualitymentioning
confidence: 98%